1997
DOI: 10.1002/hep.510250120
|View full text |Cite
|
Sign up to set email alerts
|

Excess Weight Risk Factor for Alcoholic Liver Disease

Abstract: PATIENTS AND METHODSThough the hepatotoxicity of ethanol has been established, only 8% to 20% of chronic alcoholics develop cirBetween January of 1982 and May of 1995, a total of 2,848 patients rhosis. The aim of this study was to assess whether being were admitted to the Hepatogastroenterology Unit of the Antoine overweight is a risk factor for alcoholic liver disease. Béclère Hospital in Clamart, France, for alcoholism or alcoholic liver One thousand six hundred four alcoholic patients were disease. To be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
3
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(190 citation statements)
references
References 1 publication
7
173
3
7
Order By: Relevance
“…Importantly, our data refutes previous assertions about possible precipitants of AH, in particular, that binge drinking precipitates the disease, and also that paracetamol use may cause it [10]. Other papers describe risk factors – for example, BMI [9, 11] – without addressing precipitants.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Importantly, our data refutes previous assertions about possible precipitants of AH, in particular, that binge drinking precipitates the disease, and also that paracetamol use may cause it [10]. Other papers describe risk factors – for example, BMI [9, 11] – without addressing precipitants.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been suggested that acetaminophen use in alcoholics can trigger AH [10]. Other studies have investigated risk factors for AH, finding that female gender and body mass index (BMI) increased the risk of incident AH [11] but without addressing the potential triggers of AH. There is no data reporting on dynamic changes in behaviour before an episode of AH.…”
Section: Introductionmentioning
confidence: 99%
“…This amount is based on epidemiological studies showing that alcohol-induced steatosis occurs above this threshold [4,5]. Owing to its increasing prevalence and strong association with the metabolic syndrome [6], it is now recognized that NAFLD/NASH can occur in association with other CLD [2], and that in some circumstances (chronic hepatitis C [7], hemochromatosis [8], alcoholic liver disease [9]) this association can increase liver damage [10]. …”
Section: Definition Epidemiology and Natural Historymentioning
confidence: 99%
“…Actually, several clinical studies suggest a strong causative link between the consumption of alcohol and progressive liver disease in individuals with high fat intake and/or diabetes [2,10,11]. In subjects with heavy alcohol consumption, obesity is an independent risk factor for the development of both acute alcohol-induced hepatitis and cirrhosis [10,12].…”
Section: Combined Effects Of Alcohol and Excessive Calorie Intake On mentioning
confidence: 99%
“…In subjects with heavy alcohol consumption, obesity is an independent risk factor for the development of both acute alcohol-induced hepatitis and cirrhosis [10,12]. Combined effects appear to affect all pathophysiological steps of disease development and progression, starting with hepatic steatosis [13].…”
Section: Combined Effects Of Alcohol and Excessive Calorie Intake On mentioning
confidence: 99%